Knowledge, attitude and practice of hemovigilance among health care professionals and hemovigilance study in a tertiary care hospital - Moqthadeer Ahamed, Syed; Manjunatha, Poornachandra Somwarpet; Milton, Beulah; Ranjini, Siva (International Journal Of Community Medicine And Public Health, 2025)
Background: Clinical staff’s wisely varying transfusion techniques result in the misuse of blood products and endanger patient safety. Hemovigilance seeks to improve the quality and safety of blood transfusions. This study aimed in order to find out the knowledge, attitude and practice of hemovigilance among HCP’s and to know the incidence and prevalence of ATR in a tertiary care hospital. Methods: An observational study of 120 HCP’s is planned to be conducted at Hospital. Pre-validated KAP questionnaire were issued. The frequency of ATR was recorded in TRRF form. At end of the study through collected data, we will subject it to statistical analysis. Results: From the view of 120 HCP, only 40 % had knowledge on the hemovigilance, and a whopping 74% is not practicing Hemovigilance safety measures. But we are happy to see that 71% have a positive attitude. Out of 40 transfusion reactions, a majority of patients had encountered FNHTR and allergic reaction, that is of 30%. Followed by delayed haemolytic reaction, TACO, TAD of 10%. And 5% did get hypotensive reaction and TRALI. Coming to type of blood component administered PRBC (60%), whole blood and FFP 20% each were seen. Out of 40 ,30 female patients (75%) and 10 (25%) reported ATR. Conclusions: Even though The HCP have positive attitude towards blood safety, the knowledge and practice of HCP is proven to be poor. The frequency of ATR showed although they are less severe if no strict monitory actions are not taken, they may turn life threatening.